PENGARUH KUALITAS PELAYANAN BELLBOY TERHADAP KEPUASAN TAMU DI HOTEL NOVOTEL MANADO - Martini, Sri; Lagarense, Bet El; Walandouw, Lindo (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2023)
The purpose of conducting this research is to analyze the influence of bellboy service on guest satisfaction at Manado Novotel Hotel. In this research, the writer used a quantitative research method with two kinds of sources in collecting the data. That is the primary source and secondary source. In an analysis of this research, the writer used a simple linear regression formula. The primary data was derived from the questionnaire’s distribution to the sample of 30 respondents who were hotel guests in the Manado Novotel Hotel. The secondary data was derived from various internet sources, books, and journals. The result of this research shows that the quality of service has a significant impact on guest satisfaction both variables have a positive and powerful impact. When the quality of service increases, so will guest satisfaction.